Evidence for eosinophil recruitment, leukotriene B4 production and mast cell hyperplasia following Toxocara canis infection in rats - Carlos,D. (2011)
It is well known that eosinophilia is a key pathogenetic component of toxocariasis. The objective of the present study was to determine if there is an association between peritoneal and blood eosinophil influx, mast cell hyperplasia and leukotriene B4 (LTB4) production after Toxocara canis infection. Oral inoculation of 56-day-old Wistar rats (N = 5-7 per group) with 1000 embryonated eggs containing third-stage (L3) T. canis larvae led to a robust accumulation of total leukocytes in blood beginning on day 3 and peaking on day 18, mainly characterized by eosinophils and accompanied by higher serum LTB4 levels. At that time, we also noted increased eosinophil numbers in the peritoneal cavity. In addition, we observed increased peritoneal mast cell number in the peritoneal cavity, which correlated with the time course of eosinophilia during toxocariasis. We also demonstrated that mast cell hyperplasia in the intestines and lungs began soon after the T. canis larvae migrated to these compartments, reaching maximal levels on day 24, which correlated with the complete elimination of the parasite. Therefore, mast cells appear to be involved in peritoneal and blood eosinophil infiltration through an LTB4-dependent mechanism following T. canis infection in rats. Our data also demonstrate a tight association between larval migratory stages and intestinal and pulmonary mast cell hyperplasia in the toxocariasis model.